Mutu Air Sungai melalui Konstruksi Kebijakan dan Kepedulian Masyarakat: Analisis Peran Partisipasi dalam Pengelolaan Sumber Daya Air - Sihsubekti, Sasanti; Cahyani, Esti Rahma (Idarotuna : Journal of Administrative Science, 2025)
This study explores the quality of river water by examining the role of community participation and local policy implementation in managing the Sumberkembang River, Tambakasri Village, Malang Regency, Indonesia. Pollution from domestic waste and clove oil industry effluents has severely affected the river, highlighting the need for collaborative solutions. Data were collected through surveys, interviews, and field observations involving 100 respondents. Results show that 98% of participants have a strong understanding of water quality issues, with 52% actively involved in regular environmental activities. Employing a SWOT analysis combined with surveys, interviews, and observations (n=100), the research identifies internal and external factors influencing governance. Results show high community awareness (98%) and regular participation (52%), but also highlight structural challenges such as limited education and waste infrastructure. The IFE score (3.10) and EFE score (3.35) indicate strong internal capacity and external support. These findings support a "growth strategy" pathway for environmental co-governance. The study contributes to the literature on participatory water management and offers practical insights for rural environmental policymaking